METODOLOGI HUKUM ISLAM MENURUT ALIRAN DEOBANDI DI MALAYSIA: Islamic Jurisprudence Methodology: An Analysis of Deobandi School in Malaysia - Che Age, Ahmad Zulkernain; Man, Saadan (Jurnal Fiqh, 2024)
The significant influence of Deobandi scholars, known for their expertise in Hadith and the Quran, raises the question of what legal methodology is adhered to by the scholars of this school. A comprehensive legal methodology typically consists of uṣūl al-fiqh, qawā’id al-fiqhiyyah and maqāṣid al-syāri’ah. Today, the community has witnessed the rejection by some of these scholars by some of these scholars towards local practices such as maulīd ar-rasūl, tahlil and so on. This study has several importance implications, serving as a reference for future researchers, JAKIM, the State Department of Islamic Religion, and graduates of the Deobandi school itself. This study took the form of a qualitative study and involved interviews with nine Deobandi respondents. The results indicate that the Deobandi school does not employ a complete legal methodology, and there is inconsistency among the respondents when applying the legal methodology in the absence of the Qur'an and Hadith. These suggests that, maqāṣid al-syāri’ah is largely overlooked by the majority of the respondents.